Analisis Kualitatif Implikasi Information Overload pada Pengguna Social Networking Sites (SNS) - Shafa Dinda Tsabitah; Diah Priharsari; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The COVID-19 pandemic has significantly changed human life, especially changes habits in using technology. However, nowadays, the use of technology, especially information technology, is increasing along with the increasing curiosity about COVID-19 information. The existence of Social Networking Sites (SNS) provides convenience for users to find and obtain the desired information. The use of Social Networking Sites (SNS) not only has a positive impact but also have a negative impact. Through this research, it can be proven that Social Networking Sites (SNS) can have a negative impact on their users. This study also aims to find out how information overload can occur in Social Networking Sites (SNS) users and how information anxiety and discontinuous usage can occur in Social Networking Sites (SNS) users who experience information overload. The research data was obtained using a qualitative analysis method using a semi-structured interview technique targeted at Social Networking Sites (SNS) users who feel information overload due to COVID-19 information. These data were analyzed using the stages of thematic analysis. The findings in this study resulted in seven categories, namely SNS characteristic, information overload, SNS characteristics causing information overload, information anxiety, information overload causing information anxiety, discontinuous usage, information overload causing discontinuous usage.